The effect of mindfulness on social media addiction among Chinese college students: A serial mediation model - Chang, Hongming; Meng, Xiaolu; Li, Yaqi; Liu, Jiaxi; Yuan, Wen; Ni, Jian; Li, Chunlu (Frontiers in Psychiatry, 2023)
The COVID-19 pandemic has exacerbated social media addiction (SMA), making it urgent to find effective interventions for social media addiction. Evidence has shown that mindfulness might be an effective intervention for social media addiction. However, psychological mechanisms by which mindfulness reduce social media use remain unclear. Here, we further addressed this issue to examine whether attentional control and fear of missing out (FOMO) mediate the relationship between mindfulness and SMA. We recruited 446 college students from two universities in China and analyzed the data. The results suggest that there are mediation effects of attentional control and FOMO between mindfulness and SMA through 3 paths: path 1, mindfulness→ attention control → SMA (-.04); path 2, mindfulness → FOMO → SMA (-.22); and path 3, mindfulness → attention control → FOMO → SMA (-.05). Therefore, mindfulness-based interventions may be an effective way to alleviate social media addiction, especially mindfulness-based interventions targeting FOMO. At the end of the article, we also discussed the limitations of this study.